(3GdSja GdeTghQ Ydi GdRfOjb hGdSGH ddQShds - (3eMjj GdOjf eMeO Hf bGSe GdeYQha HCNhjf,J (B904 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdfGUQ dChdjGFg GdbGHQ dCYOGFg s
(3BNQgG (B:s
(3cGdJUQjM hbGd HYVge GdJKbd EdN s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1019s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdChbGa HWQGHdS GdZQH (B- (3djHjG (B(69) s
Keywords: (3Gdabg GdMfajs